Emergence and genomic diversification of a virulent serogroup W:ST-2881(CC175) Neisseria meningitidis clone in the African meningitis belt. Issue 8 (21st June 2017) - Lamelas, Araceli; Hauser, Julia; Dangy, Jean-Pierre; Hamid, Abdul-Wahab M.; Röltgen, Katharina; Abdul Sater, Mohamad R.; Hodgson, Abraham; Sie, Ali; Junghanss, Thomas; Harris, Simon R.; Parkhill, Julian; Bentley, Stephen D.; et al.
Abstract : Countries of the African 'meningitis belt' are susceptible to meningococcal meningitis outbreaks. While in the past major epidemics have been primarily caused by serogroup A meningococci, W strains are currently responsible for most of the cases. After an epidemic in Mecca in 2000, W:ST-11 strains have caused many outbreaks worldwide. An unrelated W:ST-2881 clone was described for the first time in 2002, with the first meningitis cases caused by these bacteria reported in 2003. Here we describe results of a comparative whole-genome analysis of 74 W:ST-2881 strains isolated within the framework of two longitudinal colonization and disease studies conducted in Ghana and Burkina Faso. Genomic data indicate that the W:ST-2881 clone has emerged from Y:ST-175(CC175) bacteria by capsule switching. The circulating W:ST-2881 populations were composed of a variety of closely related but distinct genomic variants with no systematic differences between colonization and disease isolates. Two distinct and geographically clustered phylogenetic clonal variants were identified in Burkina Faso and a third in Ghana. On the basis of the presence or absence of 17 recombination fragments, the Ghanaian variant could be differentiated into five clusters. All 25 Ghanaian disease isolates clustered together with 23 out of 40 Ghanaian isolates associated with carriage within one cluster, indicating that W:ST-2881 clusters differ in virulence. More than half of the genes affected by horizontal gene transfer encoded proteins of the 'cell envelope' and the 'transport/binding protein' categories, which indicates that exchange of non-capsular antigens plays an important role in immune evasion.